Analisis Penerapan Strategi Marketing Mix Dan STP (Segmentation , Targeting, Positioning) Pada Cafe 1960 Di Banjarbaru - jumiati; Rahmah, Aulia; Agustin, Ayu Noor (Universitas Achmad Yani Banjarmasin, 2024)
Research objectives: To find out digital marketing at Cafe 1960 Banjarbaru to attract consumers; To find out the results of the analysis using the 4P analysis method (Price, Product, Place, Promotion) and the STP analysis method (Segmentation , Targeting, Positioning). Marketing carried out by Cafe 1960 Banjarbaru to attract consumers with promotions via social media with Instagram has been carried out by Cafe 1960 Banjarbaru to attract customers by providing promotions on certain holidays; The marketing strategy using the 4P analysis method that this Café perceives is a promotional strategy and a place strategy. It is felt that the promotional strategy of using other menu offers from k+366e to consumers can be used as a promotional strategy for Cafe 1960 Banjarbaru, if seen from the 94 respondents who answered Yes, 82 respondents or 87.2% of respondents who answered Yes. And the strategy where 94 respondents answered Yes or 100% of respondents answered Yes; Marketing Strategy with STP Analysis draws conclusions, segmentation by identifying market potential into certain parts based on geography, psychology and behavior. The target market is all young people who can enjoy Banjarbaru coffee and food; the results of the positioning interview were divided into 7 types: attributes, benefits, use or application, users, competitors, product categories as well as quality and price. The application of the 7 types of positioning was in accordance with the theory used by Cafe 1960 Banjarbaru